Penerapan Antara Micro Habit Dan Metode Itqon Dalam Penguatan Hafalan Al-Qur’an - Koyubi, Kholid; Alek Maulana; Nana Mulyana (Rayah Al-Islam, 2026)
The reason for this research is that many of santri (Islamic boarding school students) have not been able to maintain their memorization of the Qur'an. Although they have reached some memorization targets, it means that there is a need for a learning strategy that is not only aimed at adding memorization but also strengthening and maintaining. This research aims to study the implementation of micro habits and the Itqon method in strengthening the memorization of the Al-Qur'an of santri at Pondok Pesantren Rumah Al-Qur'an Daarut Tarbiyah, Depok. The study used a qualitative approach and case study design. The data collection techniques include observation, in-depth interviews, and documentation. The data analysis techniques are data reduction, data display, and conclusion drawing. The results showed that the micro habits implemented through daily muroja'ah, gradual memorization targets, and structured time management were able to improve the discipline, consistency, and independence of santri in maintaining their memorizationAs for the Itqon method which was performed using the techniques of tatsbit, tasmi' and periodic evaluation, it was effective in improving the quality of memorization and its long-term retention. The integration of the two approaches created synergy which supports the improvement of memorization retention and also the shaping of the Qur’anic character such as istiqamah (steadfastness), responsibility and discipline. The newness of this study lies in the integrative analysis of micro habits and the Itqon method in tahfidz learning. The results of this study contribute to the development of a more systematic sustainable tahfidz learning model oriented to the quality of memorization and the formation of santri's character.